Constitutionalism of disaster in Ecuador: state conduct and sentences during the COVID-19 health emergency - Guerrero Salgado, Efrén Ernesto (2022)
This article reviews the concept of “disaster constitutionalism” in the COVID-19 pandemic scenario in Ecuador. The predominant feature of this scenario was public actors immersed in a context in which the rules of legality, administrative controls and (emergency) solutions generated situations of systemic inefficiency. This article examined the inability to address the needs of citizens and the violation of the constitutionally established principle of legality. With that aim, this research used the concept of “necroconstitutionalism”, which refers to a power that denies politics, subjects, and their rights. This paper reviewed Constitutional Court of Ecuador (CCE) rulings, especially sentence No. 34-20-IS/20, regarding the use of public funds to meet emergency needs. In conclusion and within public administration, disaster constitutionalism restricts living conditions, generates institutions, and undermines the rights of citizens.